South-south Cooperation and Chinese Foreign Aid
XX, 281 p. 12 illus.
Keywords: This book is a collection of 15 case studies on China’s foreign aid and economic cooperation with developing countries. Each case introduces the general information of a China’s project, analyzes its features and impacts, and especially focuses on analysis of the characteristics of China’s foreign aid under South-South Cooperation framework, which shows the differences of foreign aid by emerging economies from that by traditional donors in aid ideology, principles, practices, and effects. This book is one of the research projects by China International Development Research Network (CIDRN), as part of its contribution to the activities under the Network of Southern Think-tanks (NeST). Meibo Huang is Director and Professor in International Development Cooperation Academy of Shanghai University of International Business and Economics. She is a deputy Secretary General of the China Society of World Economics and a key member of the China International Development Research Network (CIDRN). Dr. Huang’s current research focuses on Chinese development cooperation, Chinese development financing and Chinese trade and investment in Africa. Xiuli Xu is Professor and Deputy Dean of China Institute for South-South Cooperation in Agriculture (CISSCA)/ China Belt and Road Institute for Agricultural Cooperation (BRIAC) at China Agricultural University. She is a key member of China International Development Research Network (CIDRN) . Her main research interests are China’s overseas investment and foreign aid, evolution of development thinking, and developmental state building. She is the initiator of the public knowledge platform: IDT (International Development Times), which disseminates frontier debates about development studies in China. Xiaojing Mao is a senior research fellow and Deputy Director of the Institute of International Development Cooperation, CAITEC, the think-tank affiliate to the Ministry of Commerce of China. Her research focuses on international development cooperation and China’s foreign aid policies. She has participated in many important aid policy studies entrusted by the Ministry of Commerce, including White Papers on China’s Foreign Aid and on China’s Mid- and Long-term Country Programs.